Mandapa (pillared hall) in the Shiva Temple of Charchoma - Temples of India Project Team (Jio Institute, 2024)
The mandapa (pillared hall) in the Shiva Temple of Charchoma is a rectangular hall featuring a stone platform at its centre. Four pillars stand at each corner of the platform, presently covered with decorated cloth pieces. The pillars are topped with brackets supporting the ceiling which follows the trabeated system of constructions.